STUDY ON REDUCTION OF IRON ORE CONCENTRATE IN ROTARY KILN TO PRODUCE DIRECT REDUCED IRON - Nuryadi Saleh; Siti Rochani (Puslitbang tekMIRA, 2019)
A direct reduced iron (DRI) was prepared using iron concentrate pellets and a coal as a reductant through three stages, namely, the first: iron concentrate pellets were dried by slow heating at 150°C to remove water content, the second: they were heated at 1,200°C to reduce magnetite into hematite which was treated in two different conditions, namely by oxygen and without oxygen injections; and the third: they were reduced in an atmosphere of CO/CO2 at various temperatures of 950-1,200°C. In this reduction process of iron oxide would be reduced by CO to metallic iron (Fe). The experimental results showed that the metallization without oxygen injection produced the best metallization at 1,100°C and the ratio of carbon/iron (FC/Fe) of 0.52 to result 84.54%, contained 74.68% Fe and 88.34% Fetotal. The metallization by oxygen injection produced the best metallization at 1,100°C, providing result of 96.81%, Femetal of 87.88% and 90.78% of Fetotal. The iron oxides on the DRI were relatively low, namely 2.9%. In this research, prior pellets preparation a magnetic oxidation process on iron ore concentrate was also conducted and changed the magnetite into hematite. The reduction process on its pellets produced 94.15% metallization at 1,100°C, and the DRI contained 97.85% of Fetotal, 85.32% of Femetal and 5.35% of Fe oxides. Furthermore, analyzing a remained carbon of the DRI using microscopy to seek the metal structure formed. The remained carbon was reported around 1-6% C. Next smelting process, it is suggested to have a high residual carbon concentration as there will be a carbon boil mechanism to reduce iron oxides that are still lagging on the DRI.